2000
DOI: 10.1115/1.1308038
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Features of Compliant Foil Bearings—Theory and Experiments

Abstract: The paper presents an analytical and experimental investigation aimed at eliciting the thermal characteristics of air lubricated compliant foil bearings. A Couette Approximation to the energy equation is used in conjunction with the compressible Reynolds equation to obtain a theoretical temperature distribution in the air used as a lubricant. The effect of temperature on the thermal properties of the working fluid is included. In parallel, an experimental program was run on a 100 mm diameter foil bearing opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 7 publications
2
37
0
1
Order By: Relevance
“…The technique was developed by Pinkus and Bupara [15] and is based on the assumption that the effect of pressure gradients on the shear rate of the fluid is much smaller compared with the runner drag effect. The Couette Approximation was applied successfully for predicting the temperature distribution in the air film of compliant foil journal bearing and compliant foil seals [16,17]. Accordingly, the temperature distribution in the air film is expressed as, [17]:…”
Section: Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The technique was developed by Pinkus and Bupara [15] and is based on the assumption that the effect of pressure gradients on the shear rate of the fluid is much smaller compared with the runner drag effect. The Couette Approximation was applied successfully for predicting the temperature distribution in the air film of compliant foil journal bearing and compliant foil seals [16,17]. Accordingly, the temperature distribution in the air film is expressed as, [17]:…”
Section: Thermal Analysismentioning
confidence: 99%
“…The Couette Approximation was applied successfully for predicting the temperature distribution in the air film of compliant foil journal bearing and compliant foil seals [16,17]. Accordingly, the temperature distribution in the air film is expressed as, [17]:…”
Section: Thermal Analysismentioning
confidence: 99%
“…Such was the conclusion made by Salehi who used a Couette Approximation to the energy equation to analytically predict resulting temperatures in a foil air bearing. Based on his work he estimates that 80 percent of the heat is absorbed via conduction into the journal and bearing and the rest is carried away with the air exiting as side leakage (ref 7). Therefore, considering its placement in an engine it is probable that the bearing and Journal will be running hotter than the surrounding environment.…”
Section: N As A/tm-2004-2131 Gomentioning
confidence: 99%
“…They also found that load capacity dropped slightly with temperature. An experimental investigation was presented by Salehi, et al, (2001) about the thermal characteristics of bump foil air bearings. A 100 mm diameter foil bearing operated at speeds up to 30 krpm employing cooling air across the bearing between top foil and bump foil.…”
Section: Experimental Studies Of Thermal Characteristicsmentioning
confidence: 99%
“…This predicted result of temperature could be useful in the design of compliant foil seals and foil bearings. An analytical investigation was done by Salehi, et al, (2001) about the thermal characteristics of bump foil air bearings with cooling fluid. In parallel, an experimental program was performed.…”
Section: Experimental Studies Of Thermal Characteristicsmentioning
confidence: 99%